IMPORTANCE OF MOUNTAIN TOURISM IN ROMANIA TO THE NATIONAL ECONOMY - Ungureanu, Adrian (Economics of Agriculture, 2015)
Why is mountain tourism so important? Here is a question which the author tried to answer to,bringing into account some scientifc arguments to support my point of view. First of all, the Carpathians have a variety of large areas of wildness, therefore, of many balanced ecosystems which acomodate all or almost all species and habitats. Their greatest value lies in the fact that they have existed and they still exist in a natural way, and their normal cycle of life flows as close to normal as possible. So, in full symbiosis with these ecosystems, winter sport tourism represents a niche that Romania does not fructify enough. Information base has formed scientifc publications of Romanian and foreign authors related to the problem under consideration and the supplies statistics tourist potential of INS, data reports county division of statistics from 2004 to 2014 and other offcial documents in Romania, Regional Development Ministry materials and public administration, as well as forecasts, authors calculations and estimates.